2010
DOI: 10.1097/ss.0b013e3181e04a2d
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Soil Structure and Fertility After Conversion of Native Sandy Desert Soil to Irrigated Cropland in Arid Region, China

Abstract: Assessment of soil quality and its direction of change with time is a primary indicator of sustainable agricultural land management. In this study, the temporal changes in soil physical and chemical properties were determined after conversion of native desert soils to irrigated croplands in a marginal oasis of the arid region, northwest China. Soil samples were collected from seven closely located farm fields that had been cultivated for 3, 5, 10, 14, 23, 30, and 40 years after agricultural cultivation, from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 36 publications
(50 reference statements)
3
58
1
1
Order By: Relevance
“…However, the obvious increase occurred at 0-20-, 20-40-and 40-200-cm depths in 80-and 100-year farmlands. The sequestration of SOC and TN in the topsoil was also observed in other oasis farmlands in northwest China (Su et al 2010;Li et al 2010;Xu et al 2011), but was contrary to the result observed by Lobe et al (2001) who found that prolonged arable cropping leads to severe SOC loss in dry regions with sandy soils in the South African Highveld, and reached equilibrium after 34 years, but the loss continued if the cropping was prolonged even after almost 100 years. Generally, ecosystem C sequestration is determined by the law of mass conservation and the availability of key nutrient elements, such as N or P (Hessen et al 2004;Kirkby et al 2011).…”
Section: The Changes In Soc and Tn Stocks Over 100 Years' Cultivationcontrasting
confidence: 52%
See 2 more Smart Citations
“…However, the obvious increase occurred at 0-20-, 20-40-and 40-200-cm depths in 80-and 100-year farmlands. The sequestration of SOC and TN in the topsoil was also observed in other oasis farmlands in northwest China (Su et al 2010;Li et al 2010;Xu et al 2011), but was contrary to the result observed by Lobe et al (2001) who found that prolonged arable cropping leads to severe SOC loss in dry regions with sandy soils in the South African Highveld, and reached equilibrium after 34 years, but the loss continued if the cropping was prolonged even after almost 100 years. Generally, ecosystem C sequestration is determined by the law of mass conservation and the availability of key nutrient elements, such as N or P (Hessen et al 2004;Kirkby et al 2011).…”
Section: The Changes In Soc and Tn Stocks Over 100 Years' Cultivationcontrasting
confidence: 52%
“…In addition, Su et al (2010) and Li et al (2013) observed that the potential for soil carbon storage and fertility improvement in the process of desert soil cultivation were controlled to a large extent by silt and clay contents. In the present study, the irrigation water from the Cele river contains much silt and clay with 4.23~5.45 g SOC kg −1 and 0.25~0.37 g N kg −1 during flood season (Shi and Gong 1995).…”
Section: The Changes In Soc and Tn Stocks Over 100 Years' Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fertilizer type and fertilization rate also contribute considerably to soil C and TN levels in cropland. According to the conventional cultivation custom, approximately 516 kg N ha −1 and 86 kg P 2 O 5 ha −1 are applied during the maize growing season, including one base fertilization of urea and di-ammonium phosphate and three topdressings of urea later in Gaotai (Li et al, 2009 , 60-90 kg K 2 O ha −1 and 3-6 t ha −1 farmyard manure in cropland of Linze each year (Su et al, 2010b and 21 g N kg −1 are applied each year (Su et al, 2006). Application of organic manure combined with mineral fertilizers has been shown to be effective in increasing both TN and the labile and recalcitrant pools of topsoil OC under conventional management (Su et al, 2006;Yang et al, 2007;Zhou et al, 2013).…”
Section: Influence Of Agricultural Management Practicesmentioning
confidence: 99%
“…Li et al (2009) found that crop rotations increased SOC and TN densities by 30-65% and 61-64%, respectively, in the 0-30 cm soil during the 10 years of cultivation after the desert was transformed into irrigated cropland. The SOC and TN contents in the topsoil of sand-fixing shrubs, irrigated cropland and shelter forest increased with time after the reclamation of desert land (Su et al, 2007(Su et al, , 2010a(Su et al, , 2010b. Su et al (2009) reported that SOC and TN accumulated at rates of 0.4 Mg C ha −1 year −1…”
Section: Introductionmentioning
confidence: 99%